2021
DOI: 10.3390/catal11060724
|View full text |Cite
|
Sign up to set email alerts
|

Testing PtCu Nanoparticles Supported on Highly Ordered Mesoporous Carbons CMK3 and CMK8 as Catalysts for Low-Temperature Fuel Cells

Abstract: Pt(Cu) nanoparticles supported on CMK3 and CMK8 ordered mesoporous carbons (OMCs) have been synthesized by electroless deposition of Cu followed by galvanic exchange with Pt. The structural characterization by high-resolution transmission electron microscopy and X-ray diffraction showed the formation of Pt(Cu) nanoparticles of 4–5 nm, in which PtCu alloys with contracted fcc Pt lattice and 70–80 at.% Pt was identified. The X-ray photoelectron spectroscopy analyses indicated that the Pt(Cu) nanoparticles were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…Its surface is rich in oxygen-containing functional groups, and these groups improve the interaction between the active component and the carrier through the oxidation and removal of CO and other reaction intermediates to achieve better antipoisoning ability. [36][37][38] It has important application prospects in adsorption and separation, catalyst carriers, and electronic devices. Lo et al synthesized highly dispersed Pt-RuOu-SnOv nanoparticles using mesoporous carbon CMK-3 as a carrier, and the best Pt-based catalysts were obtained by modulating the electronic structure by varying the content of Ru and Sn.…”
Section: Mesoporous Carbonmentioning
confidence: 99%
“…Its surface is rich in oxygen-containing functional groups, and these groups improve the interaction between the active component and the carrier through the oxidation and removal of CO and other reaction intermediates to achieve better antipoisoning ability. [36][37][38] It has important application prospects in adsorption and separation, catalyst carriers, and electronic devices. Lo et al synthesized highly dispersed Pt-RuOu-SnOv nanoparticles using mesoporous carbon CMK-3 as a carrier, and the best Pt-based catalysts were obtained by modulating the electronic structure by varying the content of Ru and Sn.…”
Section: Mesoporous Carbonmentioning
confidence: 99%
“…25,[49][50][51][52] For small PtCu NPs (2-5 nm), obtained also by galvanic displacement of Cu by Pt on different carbon supports, X-ray photoelectron spectroscopy (XPS) analyses with different Ar + sputtering times were performed. 25,[49][50][51][52] Interestingly, the XPS results showed that the Pt(0):Cu(0) ratio decreased when increasing the sputtering time, thus strongly indicating a Pt surface enrichment. Thus, the NPs can be described as having core@shell structures with a PtCu alloy core and a shell mainly composed of Pt atoms.…”
Section: View Article Onlinementioning
confidence: 99%
“…Besides, the size of the NPs studied in this paper was too small to detect Pt and Cu concentration gradients along the NP diameter (line profile) by energy-dispersive X-ray spectroscopy (EDS) because of insufficient spatial resolution of the technique. 25,[49][50][51][52] For small PtCu NPs (2-5 nm), obtained also by galvanic displacement of Cu by Pt on different carbon supports, X-ray photoelectron spectroscopy (XPS) analyses with different Ar + sputtering times were performed. 25,[49][50][51][52] Interestingly, the XPS results showed that the Pt(0):Cu(0) ratio decreased when increasing the sputtering time, thus strongly indicating a Pt surface enrichment.…”
Section: Co Stripping Voltammograms On Reference Pt and Ptcu Bimetall...mentioning
confidence: 99%
“…The interest in copper (Cu) being used in combination with different metals, such as gold, palladium, platinum or silver, has increased in recent years. [22][23][24] The presence of copper can decrease the cost of the catalyst and improve the catalytic activity in many reactions, i.e. selective hydrogenolysis of biomass-derived glycerol or reduction of 4-nitrophenol by NaBH 4 .…”
Section: Introductionmentioning
confidence: 99%